The Impact of Pruning Intensities and Non-Nutrient Ameliorants on Brazilian Spinach Growth in Floating Cultivation System - Muda, Strayker Ali; Lakitan, Benyamin; Wijaya, Andi; Susilawati, Susilawati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Brazilian spinach is a highly nutritious leafy vegetable containing vitamins, minerals, and dietary fiber. This study assesses the impact of pruning intensities and non-nutrient ameliorants on Brazilian spinach growth in a floating cultivation system. The research follows a factorial randomized block design, with pruning intensity as the first factor and non-nutrient ameliorant as the second factor. Pruning intensity was categorized as light, moderate, and heavy, while the non-nutrient ameliorant included control, fine sand, rice-husk biochar, and fine sand + rice-husk biochar. The results show that moderate and heavy pruning effectively improved the response to NPK fertilization. Moderate pruning is proven to trigger the canopy area, especially starting 2 to 4 weeks after pruning. The Brazilian spinach canopy area demonstrated exponential growth and positively correlated with canopy diameter. The photosynthesis distribution in branch and shoot on moderate pruning was higher than heavy pruning, as indicated by dry weight. Moderate pruning produced a higher marketable yield than other pruning intensities. Regarding non-nutrient ameliorants, there are similarities in SPAD value, canopy area, index, dry weight, and yield. Therefore, moderate pruning is an effective practice to improve the growth and yield of Brazilian spinach, while the selected non-nutrient ameliorants have no impact.